2018
DOI: 10.1002/jper.17-0405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of d‐valine on periodontal or peri‐implant pathogens: Porphyromonas gingivalis biofilm

Abstract: Background: When presented with a surface or an interface, bacteria often grow as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Then, the cultures were inoculated into fresh BHI broth supplemented by menadione and hemin. As previously reported, the biofilm formed by bacterial colonies at 10 8 CFU/mL exhibited a tightly connected and homogeneous structure [25]. Consequently, for all assays in the present study, bacteria in Journal of Oral Science, Vol.…”
Section: Bacterial Culture and Reagentssupporting
confidence: 80%
See 1 more Smart Citation
“…Then, the cultures were inoculated into fresh BHI broth supplemented by menadione and hemin. As previously reported, the biofilm formed by bacterial colonies at 10 8 CFU/mL exhibited a tightly connected and homogeneous structure [25]. Consequently, for all assays in the present study, bacteria in Journal of Oral Science, Vol.…”
Section: Bacterial Culture and Reagentssupporting
confidence: 80%
“…Such contrary effects may be associated with the different experimental conditions and bacterial strains because the specific effects of d-amino acid are not similar for all types of bacterium. However, the results of a previous study revealed the potential role of the antibacterial effect on P. gingivalis [25]. On the basis of these extended preliminary experiments, d-arginine was selected as the target amino acid, considering that the arginine residue may have a potential role in antimicrobial property [40].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal and peri‐implant disease are inflammatory conditions associated with the soft (gingivae) and hard (alveolar bone) tissues surrounding teeth and dental implants, respectively. The classical risk factors of periodontal (gingivitis and periodontitis) and peri‐implant (peri‐implant mucositis and peri‐implantitis) diseases include bacterial overload in the oral biofilm and an immunocompromised health status (as observed in patients with acquired immune deficiency syndrome and individuals infected with the human immunodeficiency virus [HIV]) . If left uncontrolled/untreated, periodontal and peri‐implant diseases may result in tooth loss and failure of osseointegration, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The classical risk factors of periodontal (gingivitis and periodontitis) and peri-implant (peri-implant mucositis and periimplantitis) diseases include bacterial overload in the oral biofilm and an immunocompromised health status (as observed in patients with acquired immune deficiency syndrome and individuals infected with the human immunodeficiency virus [HIV]). [3][4][5][6][7] If left uncontrolled/ untreated, periodontal and peri-implant diseases may result in tooth loss and failure of osseointegration, respectively. 8,9 Although colonization and proliferation of anaerobic gram-negative bacteria in the oral biofilm is often associated with the onset and progression of periodontal and peri-implant diseases, [10][11][12][13] studies [14][15][16][17][18][19][20] have shown that viruses, such as Epstein-Barr virus (EBV), human cytomegalovirus (HCMV), and herpes simplex virus (HSV), have also been detected in subgingival oral biofilm samples of patients with periodontal and peri-implant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that D-arginine and D-valine were effective in inhibiting P. gingivalis bio lm formation and promoting the disassembly of mature P. gingivalis bio lm respectively 15,16 . Considering that different D-AAs might be involved in different metabolic forms of bacteria, we speculated that combined application of D-AAs would present synergistic effects on bio lm.…”
Section: Discussionmentioning
confidence: 99%